Review on Financial Risk Management and Analysis for Private Investors: Exploring the Impact of Socioeconomic Background on Investment Strategies and Financial Risk Management for Private Investors (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The goal of this research was to find out how a person's socioeconomic background affectstheir ability. The analysis approach that was used throughout this study is known as logistic regression.As a result, the findings of this study are able to provide customers with an optional choice about suitableinvestment as one of the strategies to promote urban community empowerment. When it comes to makinginvestments, individual investors in Hyderabad have access to a broad variety of opportunities from whichto choose. It is common practise for investors to consider Return, which refers to the potential return thatcan be achieved through investment Risk, which refers to the variation in returns that can result fromchanges in value or fluctuations in the market and Return, which refers to the potential return that canbe achieved through investment. When making selections about investments, a person's personalpreferences about risk, return potential, and the capacity to access assets at any given moment aretaken into consideration. An investment strategy is a plan that is meant to assist an investor in selectingthe best possible investment portfolio in order to assist the investor in achieving their financialobjectives within a certain amount of time. This kind of thinking is what people mean when they talkabout investment strategy. By increasing the wealth of individual residents, investing has the potentialto improve the economy as a whole and contribute to greater prosperity. It may be beneficial forcompanies to make investments in situations in which they have the opportunity to obtain capitalthrough the financial markets. Depending on the specifics of the situation, the investor, the firm, andeven society as a whole may all stand to gain from the use of different sorts of investments. Thepotential for profit or loss is something that Indian investors are well aware of, in addition to having afundamental grasp of portfolio allocations.